PRESENTATION OF CHILDREN WITH MASTURBATION - Shah, Syed Sajid; Bibi Aalia; Shehzad Najeeb (Journal of Ayub Medical College Abbottabad, 2022)
Childhood masturbations (CM) is stimulation of genital by pre-adolescent children with accompanying symptoms including sweating, tachycardia, blushing, muscle contraction and increase rate of breathing. We are presenting case series of three patient, who presented with history of vague symptoms and ultimately diagnosed and managed as case of CM. A 2 years old girl presented with history of to and fro movements. A 3 years old girl presented with history of rubbing of inner thighs and 3 years old boy presented with history of holding and rubbing genitalia with forward bending and symptoms of increase breathing, flushing and sweating. Video recording was available with two patients, which helped in making final diagnosis. Parents were counselled and patients referred for behavioural therapy. Conclusion: In young child CM should be considered in differential diagnosis whenever history is not fully suggestive of seizures.